STRATEGI GURU DALAM MENGEMBANGKAN KECERDASAN EKSISTENSIAL ANAK USIA DINI DI PAUD ISMAILIYAH MANDAILING NATAL - Rostriana, Cici; Harahap, Abdi Syahrial (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education is an important tool and a very effective tool in teaching norms, applying values, and instilling work persistence in a community group. Education is also an interaction that occurs between a teacher and students to achieve a goal in education. Students are an important factor in the world of education so that the goals of the learning process are achieved. This research aims to determine teacher strategies in developing existential intelligence in early childhood at PAUD Ismailiyah Mandailing Natal. The method used in this research is a qualitative method and a descriptive approach. The findings of this research show that developing existential intelligence in early childhood is by applying the Multiple Intelligence theory. The Multiple Intelligence concept believes that no child is stupid, because every child must have at least one advantage. If these advantages can be identified from the start, automatically the advantages will be the child's potential intelligence